FACTORS AFFECTING EMPLOYEE PERFORMANCE - Yopi Yulius (Dinasti Publisher, 2022)
The purpose of this study was to determine and analyze: (1) Placement (2) Work Discipline; (3) Employee Performance; and (4) The Effect of Placement and Work Discipline on the Performance of the Railway Engineering Center for West Java Region, either simultaneously or partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the employees of the West Java Regional Railway Engineering Center with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the placement of employees at the Railway Engineering Center for the Western Java Region was good, the Work Discipline of the Employees at the Railway Engineering Center for the Western Java Region was generally good, the employee performance of the Railway Engineering Center for the Western Java Region was currently considered good. Employee Placement and Work Discipline have an effect on the Employee Performance of the Railway Engineering Center for the West Java Region simultaneously and partially. However, partially dominant placement affects employee performance than work discipline. Because placement more dominantly affects employee performance, it becomes the first priority in improving the employee's performance. Therefore, the West Java Regional Railways Engineering Center is advised to remain consistent in arranging work placements according to their existing abilities, so that they are able to work more professionally.